2011
DOI: 10.1189/jlb.0111004
|View full text |Cite
|
Sign up to set email alerts
|

Human β-defensin-2 enhances IFN-γ and IL-10 production and suppresses IL-17 production in T cells

Abstract: Psoriasis is an inflammatory dermatosis with enhanced expression of hBD-2 in keratinocytes and infiltration of cytokine-producing T cells, which in turn, up- or down-regulate hBD-2 expression. We determined the serum levels of hBD-2 and cytokines in psoriasis patients and analyzed the effects of hBD-2 on cytokine production in human peripheral blood T cells. Serum hBD-2 levels in patients were higher than those in controls and correlated with PASI, serum IFN-γ, and IL-10 levels and correlated inversely with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 50 publications
(69 reference statements)
5
58
2
3
Order By: Relevance
“…Costimulatory molecules on T-cells (i.e., CD28) are increased in response to HNP1-3 [26,27] and the secretion of various proinflammatory peptides is promoted [26,28]. In accordance with the notion that defensins are capable of inducing the maturation/activation of antigen-presenting cells, enhanced antigen-specific humoral and cellular immune responses were found when antigen was administered in combination with HNP or mouse-homologues of beta-defensins [12,26].…”
Section: Immunomodulatory Effect Of Defensinssupporting
confidence: 58%
“…Costimulatory molecules on T-cells (i.e., CD28) are increased in response to HNP1-3 [26,27] and the secretion of various proinflammatory peptides is promoted [26,28]. In accordance with the notion that defensins are capable of inducing the maturation/activation of antigen-presenting cells, enhanced antigen-specific humoral and cellular immune responses were found when antigen was administered in combination with HNP or mouse-homologues of beta-defensins [12,26].…”
Section: Immunomodulatory Effect Of Defensinssupporting
confidence: 58%
“…The recent novel study has found a close relation between human beta defensin 2 and inflammatory cytokines in the serum of patients with psoriasis. Human beta defensin 2 acted as a stimulator by enhancing interferon gamma, TNF-alpha, IL-10, IL-1 beta, IL-6 and IL-22 production and regulator by suppressing IL-17 or stimulating IL-10 production [8].…”
Section: Discussionmentioning
confidence: 99%
“…This stimulation does not necessarily come only from bacteria since proinflammatory cytokines such as TNF-α, interferon (IFN)-gamma, IL-1β, IL-17, and IL-22, stimulate hβD-2 secretion. Otherwise, anti-inflammatory cytokines such as IL-4, and IL-10, suppress its production (28) . Besides, hβD-2 brings blood cells to the site of infection by acting as chemotactic agents (28,29) .…”
Section: Beta Defensins-2; Chronic Periodontitis; Smokingmentioning
confidence: 99%
“…Otherwise, anti-inflammatory cytokines such as IL-4, and IL-10, suppress its production (28) . Besides, hβD-2 brings blood cells to the site of infection by acting as chemotactic agents (28,29) . HβD-2 also was found to trigger fibroblast proliferation (30) .…”
Section: Beta Defensins-2; Chronic Periodontitis; Smokingmentioning
confidence: 99%